Quality of Life in Patients Undergoing Percutaneous Coronary Intervention - Vasiliki Tsoulou; Georgios Vasilopoulos; Theodore Kapadochos; Niki Pavlatou; Antonia Kalogianni; Georgia Toulia; Evangellos Dousis; George Panoutsopoulos; Michael Kourakos; Maria Polikandrioti (Clinics and Practice, 2023)
Introduction: Percutaneous coronary intervention (PCI) is a non-surgical invasive procedure to treat coronary artery occlusion. The quality of life (QoL) is a way to measure the impact of illness and additionally its treatments to traditional measures of clinical outcomes. Purpose: The aim of the present study was to explore the levels of QoL pre-PCI, 6 and 12 months after PCI, as well as the factors associated with the QoL pre-PCI. Methods: In the present study, 100 patients undergoing PCI were enrolled. Data were collected through the completion of the SF-36 Health Survey (SF-36), which included participants’ characteristics. The statistical significance level was p < 0.05. Results: Patients had moderate levels of QoL at baseline, with a median general health score of 45 (IQR: 30–65). A gradual statistically significant increase in scores was observed in all subcategories of the patients’ QoL at 6 and 12 months after PCI (p < 0.001). A greater increase in scores was observed in physical functioning, physical role, emotional role and social functionality. In terms of the pre-PCI phase, it was found that physical functionality was statistically significantly associated with educational level (p = 0.005), occupation (p = 0.026) and whether the patients had children (p = 0.041). The physical and emotional role was significantly associated with gender (p = 0.046 and p = 0.040) and educational level (p = 0.030 and p = 0.001). Energy–fatigue was significantly associated with gender (p = 0.001), age (p = 0.028), marital status (p = 0.001), educational level (p = 0.001), whether the patients had children (p= 0.012) and other diseases (p = 0.001). Emotional well-being was significantly associated with family history of coronary artery disease (p = 0.011) and the frequency of physical exercise (p = 0.001). Social functioning was significantly associated with gender (p = 0.033), marital status (p = 0.034) and educational level (p = 0.002). Pain was not found to be significantly associated with patients’ demographics. General health was significantly associated with gender (p = 0.003), age (p = 0.043), educational level (p = 0.001), other diseases (p = 0.005) and the frequency of physical exercise (p = 0.001). Conclusion: Information about the QoL of PCI and its determinants is important to define an effective and comprehensive care plan.